Performing DALK complicated by Descemet's membrane macroperforation in keratoconus without conversion to penetrating keratoplasty: a case report - V. N. Serdiuk; N. G. Klopotskaya; S. B. Ustimenko; Ye. N. Maidenko; Ye. B. Storozhenko; V. V. Tikhomirova (Ukrainian Society of Ophthalmologists, 2022)
We report a case of successful deep anterior lamellar keratoplasty (DALK) for kearatoconus in the presence of intraoperative Descemet's membrane (DM) macroperforation in a 10-year boy. Intraoperative optical coherence tomography-guided femtosecond laser-assisted DM separation from the periphery to the center facilitated keeping the anterior chamber angle open and avoiding a subsequent increase in intraocular pressure. In addition, the size of the graft was made 0.4 mm larger that the size of the trephination hole, which enabled fitting of the graft margins and trephination margins, whereas precise deep femtosecond laser corneal dissection enabled (a) preventing a shock wave effect from the laser pulses and (b) DM adherence to the stroma of the graft. At 5 months after surgery, uncorrected visual acuity (UCVA) was 0.5; keratometry values OD were R1, 7.67 mm; К1, 44.0 D; R2, 7.30 mm; К2, 46.2 D; Rm, 7.48 mm; Km, 45.1 D; and Astig, 2.2 D. Anterior chamber angle was 41.4º. The DM adhered well to the donor stroma, the DM defect was practically not visualized on imaging, and endothelial cell density was 2719 cells/mm2 in the operated eye. At 7 months after surgery, the patient's UCVA was 0.6 OD and corrected visual acuity with a spherical equivalent of +3.0 D was 0.9.